MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN COOPERATIVE SCRIPT PADA SISWA SEKOLAH MENENGAH ATAS - Muhammad Fathurrahman (Universitas Muhammadiyah Sorong, 2016)
The research aimed to describe the cooperative learning script that can improve student mathematic learning out comes.The research was conducted in sorong, the subyek of this research was X grade at SMA Muhammadiyah Al-Amin Sorong, in academic 2013 / 2014. The student consist of 9 males and 20 female. The research was classroom action research (PTK). The procedure and implemantion at the study site was divided into two cycles. In the first cycles performed three times of implementation by using cooperative learning script. The second cycles took three times with the same model.Cooperative learning script is method of learning when the student.According to the research. The research can contlude that the student mathematic learning outcomes at SMA Muhammadiyah Al-Amin SorongÂ X grade, can improve student learning outcomes the first cycles mean of 55.34% with the presentase in learning 58.6% and of second cyclesÂ the average was of 81.93% with the presentase in learning 93.1%.